Electric Vehicle Safety from a Service-Dominant Logic Perspective: A Literature Review - Hadi Sutrisno; Sukardi Sukardi (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study aims to analyze electric vehicle (EV) safety as a component of value creation from the perspective of Service-Dominant Logic (SDL) using a literature review approach. In the context of a rapidly evolving and competitive EV industry, safety is no longer viewed solely as a technical attribute but as a critical element in shaping customer trust, satisfaction, and long-term loyalty. Accordingly, safety is positioned as an integral part of the value proposition offered to customers. The study was conducted between August and October 2025 through a systematic review of academic journals, industry reports, and relevant publications on electric vehicles and service management. The analysis employs descriptive and comparative techniques to synthesize prior research and identify key patterns. The findings reveal that EV safety is the result of a value co-creation process involving multiple actors—manufacturers, service providers, and users—within a service ecosystem. Key determinants include user knowledge and behavior, the reliability of charging infrastructure, the effectiveness of after-sales services, and the quality of digital interaction systems. These elements collectively shape customer perceptions of safety and overall value. The study further highlights that safety plays a strategic role in reducing perceived risk and strengthening customer confidence, particularly in emerging markets where adoption is still evolving. From a managerial perspective, the findings emphasize the importance of integrating safety into service-based strategies through customer education, infrastructure development, and continuous service engagement. In conclusion, managing safety as a co-created value rather than merely a technical feature enables firms to enhance customer experience and achieve sustainable competitive advantage in the EV market.